THE EFFECT OF DYSLIPIDEMIA ON THE INCIDENCE OF CORONARY HEART DISEASE IN WOMEN - Adang Muhammad Gugun; Aldina Sheina Fernanda; Nabila Ardia Pramono; Sartika Pradhipta Cahya; Vella Febri Ferryana (Cerdika: Jurnal Ilmiah Indonesia, 2024)
Coronary heart disease (CHD) is one of the non-communicable diseases that causes the highest mortality in the world. Dyslipidemia is an important risk factor for CHD. This study aims to determine the relationship of dyslipidemia in detail including increased cholesterol, increased triglycerides, increased LDL cholesterol and decreased HDL cholesterol on the incidence of CHD in women at PKU Muhammadiyah Hospital Yogyakarta. This study used a case-control design involving 58 women as research subjects. The case group consisted of 29 women diagnosed with CHD and the control group consisted of 29 women diagnosed as non-CHD patients, including chronic lung disease, pneumonia, heart failure, dyspepsia and malignancy. Data tracing through medical records was carried out in March-September 2019. The results of this study the age range in the case group was 45-84 years and in the control group was 42-90 years. Based on the Chi-Square test, there was a significant relationship between dyslipidemia (RO = 7.04 (1.73-28.6), p = 0.003), high total cholesterol levels (RO = 5.14 (1.54-17.2), p = 0.012), high LDL cholesterol levels (RO = 9.286 (2.29-37.6), p = 0.001) and the incidence of CHD in women. From the Chi-Square test there was no significant relationship between high triglyceride levels (OR=2.16 (CI:0.62-7.49), p=0.358), low HDL cholesterol levels (RO=2,554 (0.83-7.84), p=0.167) and CHD incidence in women. The conclusion of this study is the effect of dyslipidemia including increased cholesterol and LDL cholesterol on the incidence of CHD in women at PKU Muhammadiyah Hospital Yogyakarta.